Ultrastructural observations of anthers, staminodes, and pollen grains of mango (Mangifera indica L. var. Beneshan; Anacardiaceae). (1st October 2020) - Muniraja, M.; Vijayalakshmi, G.; Lakshmipathi Naik, M.; Terry, Rg.; Sha Valli Khan, P. S.
Abstract: The ultrastructure of anthers, staminodes, and pollen of Mangifera indica L. was studied using scanning electron microscopy (SEM), and pollen viability assessed using light (LM) and fluorescence microscopy (FM). Ultrastructural observation revealed anther surfaces with polygonal cells and hollow centres arranged in a reticulate manner, with swollen cells on the edges of the anther surfaces. Anther dehiscence is longitudinal, with pollen released through a long slit in both thecae. The average length and width of staminodes of male and hermaphroditic flowers measured 0.7 mm × 0.35 mm and 0.65 mm × 0.3 mm, respectively. Distinct ridge and hook-like outgrowths on the adaxial surface of staminodes are described, as are staminode surfaces comprised of long, irregular cells with stomata exuding nectar. Staminodes produced no pollen. Anthers of male flowers produced more pollen grains (536–537) than did anthers of hermaphrodite flowers (510–511). Pollen grains are tricolporate, have reticulate perforate exine ornamentation, and are bi-cellular at dispersal. Anther and staminode size and pollen production was greater but not significantly different in male versus hermaphrodite flowers. In contrast, the fluorochromatic reaction (FCR) test and FM observations found significantly higher pollen viabilities in hermaphroditic (50.1%) versus male (40.4%) flowers. This research provides new ultrastructural characters potentially useful in future taxonomic studies of mango and other Anacardiaceae. Results presented here may also be useful in pollination studies, and in the improvement of mango breeding programmes and commercial fruit production.